2021
DOI: 10.1007/s10854-021-06393-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning synthesis of Fe3O4/Eu(DBM)3phen/PVP multifunctional microfibers and their structure, luminescent and magnetic properties

Abstract: Multifunctional Fe 3 O 4 /Eu(DBM) 3 phen/PVP ((DBM: dibenzoylmethane, phen: 1,10-phenanthroline, PVP: polyvinyl pyrrolidone) micro bers were constructed by simple electrospinning process. The structure and morphology of the micro bers were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images. The diameters of pure PVP micro bers and the micro bers doped only with Fe 3 O 4 nanoparticles (NPs) were uniformly distributed, with an average si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The diffraction peaks of Fe 3 O 4 were observed in sample 20Fe40Tb, which indicated that Fe 3 O 4 nanoparticles were doped into the composite microfibers. The XRD pattern of PS microfibers showed no diffraction peaks, indicating that the PS microfibers were amorphous [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diffraction peaks of Fe 3 O 4 were observed in sample 20Fe40Tb, which indicated that Fe 3 O 4 nanoparticles were doped into the composite microfibers. The XRD pattern of PS microfibers showed no diffraction peaks, indicating that the PS microfibers were amorphous [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Functional microfibers were prepared by the electrospinning method. The electrospinning process was carried out at room temperature and relative humidity, similar to previous literatures [ 29 , 33 ]. The syringe was placed on a syringe pump and used at a flow rate of 0.6 mL/h −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation